Combination treatment with acupoint therapy and conventional medication for non-motor symptoms in Parkinson’s disease: a systematic review and meta-analysis - Wenjiao Hu; Wenjiao Hu; Hao Zhou; Wenwen Zhu; Wenwen Zhu; Songcheng Xie; Songcheng Xie; Yue Zeng; Zhengyan Wang; Zhengyan Wang (Frontiers in Neurology)
BackgroundManaging Parkinson’s non-motor symptoms (PD-NMS) is challenging. Traditional methods have limited efficacy for NMS. Acupoint therapy offers a safe and personalized option. There has been a growing number of studies on acupoint therapies for PD-NMS. However, a systematic review of their effectiveness and safety is currently not available. Therefore, this study aims to evaluate the effectiveness and safety of acupoint therapy for PD-NMS.MethodsPubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure, Wanfang Database, China Science and Technology Journal Database, and Chinese Biomedical Literature Database were searched. Data were analyzed using fixed or random effects models. Randomized controlled trials (RCT) in Chinese and English relating to acupoint therapy for NMS in PD (PD-NMS), individuals diagnosed with PD, primary and secondary outcome measures are HAMD, MMSE, MoCA, PDSS, PSQI were included. Cochrane risk-of-bias tool (ROB 2) for RCT was used. Meta-analyses were performed to calculate the RR and WMD. Subgroup analyses, sensitivity analyses, and funnel plot analyses were conducted.ResultsForty-two studies (3120 PD-NMS patients) from database establishment to May 2023 were included. According to the ROB 2 evaluation, risks of bias in random sequence generation, missing data and selective reporting were low, moderate in allocation concealment, and high in blinding. Acupoint therapy combined with CM or NDT was more effective than single-therapy in most outcome measures like effective rate, HAMD, MoCA, PDSS and PSQI, but the MMSE difference was non-significant.ConclusionDue to the large number of research subjects, differences in the severity of the diseases, and possible variations of the intervention details, there is a certain degree of heterogeneity in the research results. However, acupoint therapy or acupoint therapy combined with CM could be an option for the treatment of PD-NMS in the future.Systematic review registrationThis review protocol has been registered in PROSPERO (ID: CRD42023426305). https://www.crd.york.ac.uk/PROSPERO/.